Propuesta para la implementación de un sistema de gestión de calidad en la empresa Angar Domotik basado en la norma ISO 9001:2015 (2022)
This project was carried out with the objective of establishing a guide for the implementation of the quality management system under the criteria of the ISO 9001: 2015 standard. For this, a series of activities were carried out that allowed defining some important aspects for the organization. The research was carried out under a qualitative approach, in which meetings were held with senior management to collect the necessary information to understand the context of the organization; research and literature associated with the topic were also consulted.